(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
A perfect adhesion between the rubber of a tire and the reinforcing polymeric cord is crucial for the overall tire performance and safety. The problem of bonding rubber to textile cords is due to the big difference between the surface properties. Blending of polymers has obtained much attention because, it can be used to obtain new polymeric materials with particular properties suitable for some special purposes. The blends of Natural rubber (NR) / Polysulfide rubber (PSR) has been prepared with a verity weight ratios (100/0, 90/10, 80/20, 60/40). The characteristics of the prepared blends were investigated, such as rheological, mechanical and damping properties. It was found that the increasing of the weight percent of PSR in the blend compositions leads to the increase its adhesive strength with nylon 66 cord and also increase the hardness of the resultant blends. On the other hand, the curing time, tensile strength, elongation at break and rebound resilience were decreased.